Investor’s Intention to Adopt Online Stock Trading in Nepal - Srijana Gyawali (Journal of Corporate Finance Management and Banking System, 2024)
This study examines the effect of performance expectancy, effort expectancy, social influence, security risk, economic risk, functional risk, and investor’s intention to adapt online stock trading. This research is based upon the primary data. The primary source of the data was used to study the factors that influence the investor’s intention to adopt online stock trading in Nepal. For the purpose of collecting the responses on the study and getting into the research objectives, 89 respondents were selected as the sample size. Data were collected with the help of structured questionnaire,which was further subjected to Reliability test, Normality test, correlation regression analysis of respondents in SPSS. Results shows that Performance Expectancy and Effort Expectancy have a high degree of positive correlation with Behavioral Intention, while Social Influence, Security Risk, Economic Risk, and Functional Risk have a moderate degree of positive correlation with Behavioral Intention.